2003
DOI: 10.2135/cropsci2003.9430
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Turfgrass Color Using Digital Image Analysis

Abstract: Color is a major component of the aesthetic quality of turf and often evaluated in field studies. Digital image analysis may be an improved, objective method to quantify turf color. Studies were conducted to determine if digital image analysis with SigmaScan software (SPSS, Chicago, IL) was capable of: (i) accurately determining the hue, saturation, and brightness (HSB) levels of Munsell Plant Tissue color chips, (ii) quantifying visual color differences among zoysiagrass (Zoysia japonica Steud.) and creeping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
273
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(292 citation statements)
references
References 9 publications
10
273
1
8
Order By: Relevance
“…Each digital image covered an area of 0.9 by 1.1 m and measurements were averaged over the two photographs. A 92 cm (length) by 61 cm (width) by 61 cm (height) metal box equipped on the inside with four 9 Watt lamps was used to provide uniform lighting conditions for all the digital images taken (Ikemura, 2003;Karcher and Richardson, 2003). A Canon A570is (Canon Inc., Tokyo, Japan) camera was set to a shutter speed of 1/60, an aperture of f/2.6, ISO 200, and a focal lens of 32 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Each digital image covered an area of 0.9 by 1.1 m and measurements were averaged over the two photographs. A 92 cm (length) by 61 cm (width) by 61 cm (height) metal box equipped on the inside with four 9 Watt lamps was used to provide uniform lighting conditions for all the digital images taken (Ikemura, 2003;Karcher and Richardson, 2003). A Canon A570is (Canon Inc., Tokyo, Japan) camera was set to a shutter speed of 1/60, an aperture of f/2.6, ISO 200, and a focal lens of 32 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Digital image analysis was used to evaluate percent green cover. Images taken on 15 November of each year were analyzed using SigmaScan Pro 5 (Systat Software Inc., San Jose, CA) (Karcher and Richardson, 2003). Volumetric water content from 0 to 7.5 cm depths was recorded monthly.…”
Section: 1mentioning
confidence: 99%
“…The camera records the image, and special software analyzes the image by measuring the greenness of the leaf based on red, green, blue (RGB) colors of the picture. The RGB values are converted into hue, saturation and brightness values using a method described by Karcher and Richardson [70] to calculate the Dark Green Color index (DGCI):…”
Section: The Dark Green Color Index (Dgci)mentioning
confidence: 99%
“…Karcher and Richardson [70] and Rorie et al [23] found DGCI an accurate tool to estimate N leaf concentration in turfgrass and maize, respectively. For example, Rorie et al [23] quantified maize leaf greenness with a digital camera and image analysis software (Sigma Scan Pro 5, SPSS, 1998, San Jose, CA, USA) in terms of DGCI by modifying the digital-imaging method of Karcher and Richardson [70].…”
Section: The Dark Green Color Index (Dgci)mentioning
confidence: 99%
See 1 more Smart Citation